2013
DOI: 10.1038/onc.2013.519
|View full text |Cite
|
Sign up to set email alerts
|

Restricting direct interaction of CDC37 with HSP90 does not compromise chaperoning of client proteins

Abstract: The HSP90 molecular chaperone plays a key role in the maturation, stability and activation of its clients, including many oncogenic proteins. Kinases are a substantial and important subset of clients requiring the key cochaperone CDC37. We sought an improved understanding of protein kinase chaperoning by CDC37 in cancer cells. CDC37 overexpression in human colon cancer cells increased CDK4 protein levels, which was negated upon CDC37 knockdown. Overexpressing CDC37 increased CDK4 protein half-life and enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…Furthermore, we show that the formation of the Cdc37-Hsp90 complex is mandatory for v-Src activation. Although this finding is in agreement with the need of the Hsp90-Cdc37 interaction for kinase-dependent cell proliferation (49), alternative pathways for certain kinases may exist (37). In this context, the affinity of a kinase for ATP does not seem to correlate strictly with its chaperone dependence as different effects were observed for B-Raf kinase (50) and the Src kinase pair studied here.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, we show that the formation of the Cdc37-Hsp90 complex is mandatory for v-Src activation. Although this finding is in agreement with the need of the Hsp90-Cdc37 interaction for kinase-dependent cell proliferation (49), alternative pathways for certain kinases may exist (37). In this context, the affinity of a kinase for ATP does not seem to correlate strictly with its chaperone dependence as different effects were observed for B-Raf kinase (50) and the Src kinase pair studied here.…”
Section: Discussionsupporting
confidence: 87%
“…3G) or silencing Cdc37 (77) particularly disrupts CRAF-Hsp90 interaction. Therefore, combining previous observations (78,79) and our findings, we suggest that Cdc37, by acting as a kinase sorting factor, assists Hsp90 in conformational maturation of CRAF.…”
Section: Stability Of Folded Craf Is Insensitive To Hsp90supporting
confidence: 48%
“…Overexpression of Cdc37 enhances CDK4 stability following increased binding to Hsp90 (78). Similarly, we found that Cdc37 upon overexpression activates the MAPK pathway by enhancing binding of Hsp90 to CRAF (Fig.…”
Section: Stability Of Folded Craf Is Insensitive To Hsp90mentioning
confidence: 51%
“…[44][45][46][47] Here, we found reduced expression of Cdc37 and increased expression of HSP70 in the cytosolic fraction of chorea-acanthocytosis red cells, compared with control erythrocytes, whereas HSP90 levels were similar in both cell types (Figure 2A). Because reticulocyte levels were similar in control and chorea-acanthocytosis subjects (data not shown, see also ref.…”
Section: Resultsmentioning
confidence: 79%